Quantification of lead in cooking utensils and vegetables using square wave anodic stripping voltammetry. Issue 1 (January 2018) - Tesfaw, Belete; Mehretie, Solomon; Admassie, Shimelis
Abstract: A simple and sensitive voltammetric method using in-situ bismuth film modified glassy carbon electrode (BiFGE) and Nafion-coated bismuth film modified glassy carbon electrode (NC-BiFGE) were used to determine the amount of lead(II) present in locally produced (at Kombolcha, 376 km North of Addis Ababa, Ethiopia) and imported cooking utensils and vegetable samples before and after cooking with the utensils. The voltammetric method was validated using standard spectroscopic method and recovery tests. The amount of lead(II) found in the locally produced utensil (6.48 mg L −1 ) was very high compared to the imported utensil (0.007 mg L −1 ). Moreover, a 3–5 fold increase in the amount of lead(II) was found when different vegetables were cooked with the local utensil as a result of the leaching out of the lead(II) from the cooking utensil.